Inhibition of ovarian cancer proliferation and invasion by pachymic acid - Gao, Ai-Hua (Int J Clin Exp Pathol, 2015)
To determine the effect of pachymic acid (PA) on proliferation, cell cycle, and invasion in human ovarian carcinoma cell lines HO-8910 and explore some possible mechanisms, HO-8910 cells was treated with different concentrations of PA (0.5, 1, 2 μM). CCK-8 assay, propidium iodide staining, was applied to measuring the growth inhibiting rates of HO-8910 cells. Cell cycle was measured by flow cytometry. In addition, the activity of PA against HO-8910 cells invasion was evaluated in transwell assay. Western blot detected the proteins expression of E-cadherin, β-catenin and COX-2 of different groups treated with PA in different concentrations (0.5, 1, 2 μM) for 48 h. Our results showed that PA could effectively inhibit the in vitro growth of HO-8910 cells in dose-dependent manners in 72 h, suppressed migration and invasion of HO-8910 cells in concentration-dependent manners at 24 h, caused the increased accumulation of G1 phase cells, and caused down-regulation of β-catenin and COX-2 and up-regulation of E-cadherin expression level. Taken together, it could conclude that PA might inhibit proliferation and invasion of ovarian carcinoma cell through decreasing β-catenin and COX-2 expression and increasing E-cadherin exprssion.